Promoting Mind–body Health in Schools: Interventions for Mental Health Professionals. 2020
DOI: 10.1037/0000157-020
|View full text |Cite
|
Sign up to set email alerts
|

Emotional freedom techniques: Stress and anxiety management for students and staff in school settings.

Abstract: E motional Freedom Techniques (EFT), more commonly known as tapping, is an emerging, research-based intervention that has been found to be an effective stress and anxiety management tool for students and school personnel. EFT uses cognitive behavior therapy techniques, such as awareness building, imaginal exposure, reframing of interpretation, and systematic desensitization, while teaching the individual to self-stimulate protocol-identified acupoints (i.e., acupuncture points; Craig, 2011;Feinstein, 2004). Gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
2
0
1
Order By: Relevance
“…The results of the current study demonstrated that the training in Emotional Freedom Technique led to a reduction in the symptoms of Post-Traumatic Stress Disorder (PTSD) following emotional trauma in women affected by marital infidelity. No study directly corresponding to the present research focused on PTSD symptoms in women affected by infidelity was found; however, this study aligns with the previous findings (Akbari et al, 2023;Alamdar Baghini et al, 2021;Church, 2014;Church et al, 2016;Church et al, 2018;Church et al, 2017;Clond, 2016;Dincer & Inangil, 2021;Gaesser, 2020;Minewiser et al, 2016;Nicosia et al, 2019;Sebastian & Nelms, 2017;Study, 2017;Yavari Kermani et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the current study demonstrated that the training in Emotional Freedom Technique led to a reduction in the symptoms of Post-Traumatic Stress Disorder (PTSD) following emotional trauma in women affected by marital infidelity. No study directly corresponding to the present research focused on PTSD symptoms in women affected by infidelity was found; however, this study aligns with the previous findings (Akbari et al, 2023;Alamdar Baghini et al, 2021;Church, 2014;Church et al, 2016;Church et al, 2018;Church et al, 2017;Clond, 2016;Dincer & Inangil, 2021;Gaesser, 2020;Minewiser et al, 2016;Nicosia et al, 2019;Sebastian & Nelms, 2017;Study, 2017;Yavari Kermani et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Many psychologists believe that delivering gentle, calculated taps on particular body points creates a balance in the body's energy system. This method focuses on reconstructing the nervous system and releasing unpleasant emotions; when an individual fully accepts themselves, they have traversed half the path and expend less energy hiding their problems and flaws (Gaesser, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This paper wishes to draw attention to the following research that supports identified therapeutic approaches for future research and consideration. In particular, Dyadic Developmental Practice DDP (Philips, Milim and Hughes, 2020;Hughes, Golding and Hudson, 2019;Bomber, Golding and Philips 2020), Social Neuroscience (Cozolino, 2013), Neurosequential Model in Education (NME) (Perry, 2009), Child -Mentalization Based Treatment (C-MBT) (Bateman and Fonagy, 2013;Twemlow, Fonagy and Sacco, 2005a), Internal Family Systems (IFS) (Swartz and Sweezy, 2019;Spiegel, 2017;Wark, Thomas and Peterson, 2001), Sensorimotor Psychotherapy & Embedded Relational Mindfulness (Ogden, Goldstein and Fisher, 2013;Ogden and Fisher, 2015;Ogden and Goldstein, 2017), Mindsight (Siegel, 2010), The Polyvagal Theory (Porges, 2018;Dana, 2018;Beauchaine, Gatzke-Kopp and Mead, 2017) Attachment (Bowlby, 1970;Ainsworth and Bell, 1970;Main, 2000) and Emotional Freedom Techniques (Clond, 2016;Stapleton et al, 2017;Gaesser, 2020). Future papers would critically analyse the research that suggests implementation would greatly support child mental health and gives strength to the argument that teacher training could potentially include understanding of a number of these therapeutic approaches to improve child mental health outcomes.…”
Section: Transdisciplinary Therapeutic Approaches For Practical Use I...mentioning
confidence: 99%
“…La falta de gestión de las emociones entre estudiantes representa una preocupación tanto en el ámbito escolar como en su desarrollo personal. Esta carencia se relaciona directamente con un bajo desempeño académico, ya que las emociones no gestionadas pueden interferir con la capacidad de concentración, el rendimiento en las tareas y la interacción positiva con los demás (Gaesser, 2020). A pesar de la creciente conciencia sobre la importancia de las habilidades blandas, como la autorregulación emocional, las prácticas integradoras para desarrollar estas habilidades siguen siendo limitadas en muchos entornos educativos.…”
Section: Introductionunclassified